Effect of arbuscular mycorrhizal fungi and planting media on seedlings growth of Helicteres isora L. in the nursery. Issue 1 (November 2021) - Prameswari, D; Irianto, R S B; Tuheteru, F D; Kalima, T
Abstract: A screw tree ( Helicteres isora L.) is a small/large shrub species that grows and spreads in many Asian countries, including Indonesia (NTT and Maluku). It is a medicinal plant commonly used to treat many diseases, such as bleeding and constipation. This study aimed to determine the effect of Arbuscular Mycorrhizal (AM) fungi and planting media on the growth of screw tree seedlings in a nursery. This research was conducted at Bogor Forest Research and Development Center's nursery, Indonesia. This study consisted of two factors: AM fungi with three levels, namely control, Glomus aggregatum and Glomus clarum and growth media with two levels, namely mixed media of soil: rice husk charcoal (2:1) and mixed soil of media: rice husk charcoal: cocopeat (2:1:1). The results showed that treatment of G. aggregatum and soil mixed of media: rice husk charcoal: cocopeat (2:1:1) was significantly different from other treatments except for G. clarum and soil mixture of media: rice husk charcoal: cocopeat (2:1:1) that significantly increased height, diameter and dry weight of seedlings and the values were 97, 56, 126 and 46, 37, 127% compared to the control. Mycorrhizal dependency of screw tree was very high (126 and 127%). Generally, interaction treatment of G. clarum and mixed media of soil: rice husk charcoal: cocopeat (2:1:1) increased the growth of 11-month-old screw tree in the nursery.